1998
DOI: 10.1111/j.2042-7158.1998.tb06173.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Bioavailability of Dihydroartemisinin, meether, Artemether, Artesunic Acid and Artelinic Acid in Rats

Abstract: The pharmacokinetics and bioavailability of dihydroartemisinin (DQHS), artemether (AM), arteether (AE), artesunic acid (AS) and artelinic acid (AL) have been investigated in rats after single intravenous, intramuscular and intragastric doses of 10 mg kg(-1). Plasma was separated from blood samples collected at different times after dosing and analysed for parent drug. Plasma samples from rats dosed with AM, AE, AS and AL were also analysed for DQHS which is known to be an active metabolite of these compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 19 publications
11
122
2
1
Order By: Relevance
“…The slow elimination of AE was recently demonstrated in a rat study, which also found significant accumulation of AE in the plasma from injection sites (Li et al, 1999b). The results of a rat study conducted by daily intramuscular injections of AE at 25 mg/kg in sesame oil for 7 days confirmed and extended the results of earlier studies (Li et al, 1998b) by demonstrating that the absorption of AE from the injection site of the muscle was incomplete. This study also indicated that up to 38% of the total single dose of AE remained in the injection site for 24 hr after dosing, and 22% of the total single dose still remained in the muscle 48 hr after dosing.…”
Section: Cause Of Am and Ae Accumulation After Intramuscular Injectionsupporting
confidence: 76%
“…The slow elimination of AE was recently demonstrated in a rat study, which also found significant accumulation of AE in the plasma from injection sites (Li et al, 1999b). The results of a rat study conducted by daily intramuscular injections of AE at 25 mg/kg in sesame oil for 7 days confirmed and extended the results of earlier studies (Li et al, 1998b) by demonstrating that the absorption of AE from the injection site of the muscle was incomplete. This study also indicated that up to 38% of the total single dose of AE remained in the injection site for 24 hr after dosing, and 22% of the total single dose still remained in the muscle 48 hr after dosing.…”
Section: Cause Of Am and Ae Accumulation After Intramuscular Injectionsupporting
confidence: 76%
“…The similarities in susceptibility of different developmental stages of S. mansoni to artemether and artesunate might be explained by the fact that the 2 compounds are remarkably related in terms of chemical structures and also pharmacodynamic properties (ZIFFER et al, 1997;LI et al, 1998;VROMAN et al, 1999). In this connection, it could be speculated that other artemisinin derivatives should exhibit similar antischistosomal properties, which has indeed been confirmed in viva for arteether (XIAO et aZ., 1992) and also dihydroartemisinin (ABDEL AZIZ & EL-BADAWY, 2000).…”
Section: Discussionmentioning
confidence: 90%
“…It is known that DHA has a longer half-life of 1.15-2.37 hours, which is 7.12-to 12.68-fold longer than AS, which has a short half-life of 0.12-0.24 hours. Therefore, the effectiveness of AS has been attributed to its rapid and extensive hydrolysis to DHA 5,7,32 and also to AS itself with a high initial C max . 23,24 In this study, the pharmacokinetics and possible side effects of an intravenous infusion of AS were studied in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…4 The effectiveness of AS has been mostly attributed to its rapid and extensive hydrolysis to DHA. [5][6][7][8] Artemisinins have been used in malaria treatments with monotherapy regimen since 1983. However, the monotherapy with the artemisinin derivatives was significantly discouraged after 2001 to prevent the emergence of resistance.…”
Section: Introductionmentioning
confidence: 99%